Effect of the flow field structures on the performance of anion exchange membrane water electrolyzer - Rui DING; Tao CHEN; Yang LAN; Ziyu CHEN; Fei XIAO (Journal of Hebei University of Science and Technology)
In order to investigate the effects of different flow field structures on the performance of anion exchange membrane water electrolyzer(AEMWE) and their mechanisms, numerical analyses of AEMWE with three types of flow field structures, namely, parallel, single-path and double-path, were carried out based on computational fluid dynamics (CFD), and the best overall performance of the bipolar plate flow field structure in terms of flow velocity distribution, pressure distribution, temperature distribution, as well as hydrogen concentration and polarization performance were determined. The results show that compared with the parallel and single-path flow field, the inlet and outlet pressure drop of AEMWE under the double-path flow field structure is more moderate at 2 400 Pa, the current density is larger, the average hydrogen concentration is 1.031 8 mol/m3, and the uniformity coefficient of temperature distribution is 0.003 8. Under the double-path flow field structure, AEMWE exhibits superior control of mass and heat transfer, as well as energy consumption, resulting in the best overall performance, which provides some reference for further optimizing flow field design and produce of AEMWE.